2003
DOI: 10.1080/08880010390158919
|View full text |Cite
|
Sign up to set email alerts
|

Association of Wilms Tumor with Spinal Dysraphism

Abstract: Previous data suggested an association of vertebral anomalies with Wilms tumor. At the same time, vertebral midline fusion defects are often indicated by dermal anomalies over the spine. In the present study the prevalence of both occult spina bifida and cutaneous signs of spinal dysraphism was significantly higher in 50 Wilms patients than in 180 control children (18.0 versus 4.4%, p <.01, and 35.9 versus 17.5%, p <.02, respectively). Family investigations are needed to answer the question whether signs of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…10 Vertebral defects should be suspected when posterior midline cutaneous abnormalities, congenital anomalies of the lower extremities, or renal anomalies exist. 5 The concurrent occurrence of butterfly and hemivertebra in our patient makes an extremely rare or unique example of this association. In patients with WT, investigation of vertebral malformations should be a part of diagnostic work-up.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…10 Vertebral defects should be suspected when posterior midline cutaneous abnormalities, congenital anomalies of the lower extremities, or renal anomalies exist. 5 The concurrent occurrence of butterfly and hemivertebra in our patient makes an extremely rare or unique example of this association. In patients with WT, investigation of vertebral malformations should be a part of diagnostic work-up.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies also have suggested an association of extrarenal or intrarenal WT with overt or occult spinal dysraphism. [5][6][7][8][9] Although butterfly vertebra and hemivertebra can be included in spinal dysraphism, in these papers no association was reported between WT and these entities. Vertebral anomalies in the present case were detected during the investigations performed to evaluate the lung.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…10–12 In addition, patients with vertebral anomalies, including spina bifida, may have an increased risk of Wilms tumor. 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Existe una agrupación sindrómica catalogada como Síndrome de Currarino, caracterizada por la existencia de múltiples anomalías caudales congénitas destacando malformaciones ano-rectales, anomalías del sacro y masas presacras 2,4,8 . Publicaciones posteriores de los años 80 sugieren una relación del tumor de Wilms (nefroblastoma) con pacientes afectos de espina bífida oculta o con estigmas cutáneos de disrafia espinal, pudiendo ser demostrada estadísticamente a comienzos de la década actual 14 . La teoría más común que tiende a explicar estas conexiones tumorales con los casos de disrafia espinal, indica que la presencia de células multipotenciales del primordio neural, al ser activadas por los cambios endocrinológicos en la adolescencia, podrían facilitar la transformación maligna de estas lesiones, si no se han extirpado antes de la edad adulta 15 .…”
Section: Figura 6 Anatomía Patológica: (A) Imagen Panorámica De La Lunclassified